Is gambling an emerging public health issue for Wales, UK?. (19th September 2018) - Atherton, F; Beynon, C
Abstract: Background: Not all gambling exposes people to the same level of harm. Harm from gambling is found at the individual, social (family and friends) and community levels. This includes financial hardship, psychological distress and interpersonal conflict or relationship breakdown. The harm from gambling to wider society includes fraud, theft, loss of productivity in the workforce and the cost of treating this addiction. The annual estimated excess cost of gambling for Wales is between £40 and £70 million. Methods: This study reviews the existing data sources and literature to ascertain if gambling is an emerging public health issue in Wales. Results: In Wales 61% of adults had gambled in the last year (1.5 million people). And 1.1% of the population (30 000 people) self-report as having a problem with gambling using either the Problem Gambling Severity Index or the Diagnostic and Statistical Manual of American Psychiatric Association tools. The 'ripple effect' of gambling harm can mean friends and family are highly impacted. Conclusion: The existing data and literature together with the rapidly evolving developments in infrastructure demonstrate that gambling is an emerging public health issue in Wales. The impact on families and society warrants population level interventions to tackle this public health issue.